Development and Validation of a Novel RP-HPLC Method for Quantification of Lenacapavir in Pharmaceutical Formulations: Research Article (Journal of Pharma Insights and Research, 2025)
A simple, specific, and robust reverse-phase high-performance liquid chromatographic (RP-HPLC) method was developed and validated for the quantitative determination of Lenacapavir in pharmaceutical formulations. The chromatographic separation was achieved using a Zorbax SB C18 column (250 × 4.6 mm, 5 μm) with a mobile phase consisting of acetonitrile and ammonium formate buffer (pH 3.0) in the ratio of 30:70 v/v. The flow rate was maintained at 1.0 mL/min, and detection was performed at 269 nm using a photodiode array detector. The developed method demonstrated excellent linearity (R² = 0.99967) over the concentration range of 12.5-75 μg/mL. The retention time of Lenacapavir was found to be 4.142 minutes, with a theoretical plate count exceeding 9000 and tailing factor of 0.95. The method showed high precision with RSD values below 0.5% for both intra-day and inter-day analyses. The accuracy of the method was confirmed through recovery studies, yielding recovery rates between 99.2% and 101.5%. The limits of detection and quantification were established at 0.15 μg/mL and 0.5 μg/mL, respectively. The method remained robust under varied analytical conditions, including changes in flow rate and mobile phase composition. This validated method proves suitable for routine quality control analysis of Lenacapavir in pharmaceutical formulations